Kemahiran metakognitif dalam penyelesaian masalah Matematik bukan rutin dalam kalangan pelajar tingkatan 5 - Wahidin, Mohd. Faizal (2010)
A problem is called a problem if it fulfills the three criteria’s; acceptance, barrier and exploration. Metacognitive strategy is an important aspect and frequently used in solving mathematical problems. It is about the way student control their cognitive process while doing mathematical problem-solving. The purpose of this research is to define the used of student’s metacognitive skills in solving the mathematical nonroutine problems and to identify the types of problems in the student’s problemsolving skills. This research involves the combination of quantitative and qualitative data. It is based on Polya Model (1957) and Flavell (1976). Polya Model tells about the process of problem solving while Flavell Model talks of metacognitive levels. Three instruments were used to gather qualitative and quantitative sets of data. The first instrument is a set of mathematical non-routine problem which were used at the first phase of this research. Then, the second phase of this research, a set of Selfmonitoring Questionnaire (SMQ) and an interview were used. The finding for this research showed six Form 5 students had a close connection between metacognitive strategies in mathematical problem solving which are, predicting, planning, supervising and evaluating.